On the limits of application of Anderson and Kondo models in physics of strongly correlated electron systems - Sluchanko, Nikolay E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
We argue that the Anderson and Kondo models turn out to be irrelevant for the description of some strongly correlated electron systems and suggest the mechanism for the formation of many-body states (heavy fermions) being an alternative to the Kondo one. This mechanism involves the quantum tunneling of a heavy particle between the states in the double-well potential.